REPRESENTATION OF A HISTORICAL FIGURE IN A LITERARY TEXT: THE POETICS OF THE VERSE NOVEL “THE RULER” BY O.ABDURAZAKOV - Gofurova, Jayrona (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2025)
The article explores the poetic features of the historical verse novel The Sovereign (Hukmdor) by Uzbek poet Oraz Abdurazzakov, dedicated to the figure of Amir Temur. The focus is on the representation of a historical personality through artistic and aesthetic language, with special attention paid to genre-specific and stylistic mechanisms that combine chronicled authenticity with epic mythologization. The novel is structured around a poetic framework that integrates documentary foundations with imaginative interpretationmerges documentary foundation with imaginative interpretation, rich in allusions, cultural codes, and symbols of Eastern poetics. Amir Temur is portrayed not only as a statesman and military leader, but also as a national archetype embodying strength, justice, wisdom, and unity. The study analyzes the functioning of a symbolic system including epigraphs, rhetorical devices, and metaphors, which contribute to the construction of a multifaceted image of the ruler. It also touches on issues of intertextuality, allegory, and stylistic resonance with classical epic traditions. Special emphasis is placed on the epic,lyrical and narrative registers registers of the author’s text, where history is reimagined as a mythopoetic narrative that serves both aesthetic and ideological purposes. The author concludes that the novel fulfills a dual function: as a literary work and as a cultural-political instrument that reinforces the image of Amir Temur as a symbol of national identity, historical continuity, and collective memory. Thus, The Sovereign becomes a poetic dialogue between historical memory and national consciousness, bridging literary artistry with socio-cultural significance.